The Optimization of a Protocol for the Directed Differentiation of Induced Pluripotent Stem Cells into Liver Progenitor Cells and the Delivery of Transgenes - Irina Panchuk; Valeriia Kovalskaia; Natalia Balinova; Oxana Ryzhkova; Svetlana Smirnikhina (Biology)
The liver plays a pivotal role in metabolism, detoxification, and protein synthesis and comprises several cell types, including hepatocytes and cholangiocytes. Primary human hepatocytes in 2D cultures rapidly dedifferentiate and lose their function, making their use as a reliable cell model challenging. Therefore, developing robust three-dimensional cell culture models is crucial, especially for diseases lacking reliable animal models. The aim of this study was to optimize a protocol for the directed differentiation of induced pluripotent stem cells into liver progenitor cells, achieving the high-level expression of specific markers. As a result, we established a 2D culture of liver progenitor cells capable of differentiating into three cell types: a 3D organoid culture containing hepatocyte- and cholangiocyte-like cells and a 2D cell culture comprising stellate-like cells. To evaluate gene delivery efficiency, liver progenitor cells were transduced with various rAAV serotypes carrying an eGFP reporter cassette at different multiplicities of infection (MOIs). Our results revealed that rAAV serotype 2/2 at MOI of 100,000 achieved the highest transduction efficiency of 93.6%, while electroporation demonstrated a plasmid delivery efficiency of 54.3%. These findings suggest that liver progenitor cells are a promising tissue-like cell model for regenerative medicine and demonstrate high amenability to genetic manipulation, underscoring their potential in gene therapy and genome editing studies.